Skeletal muscle tissue engineering using biological scaffolds for repair of abdominal wall defects in a rabbit model - Tsedeke, Ayele Taddese (2009)
Abdominal wall defects caused by trauma, tumour ablation, muscle deficiency or postsurgical loss of muscle mass may lead to the need for restoration of damaged muscle tissues as loss of functional muscle tissue could cause severe impairments of the functionality of skeletal muscle. Hence, the present study was aimed mainly to engineer skeletal muscle tissue using myoblast seeded bovine pericardium (BP) and bovine tunica vaginalis (BTV) scaffolds in a rabbit model. Myoblast were harvested successfully from soleus muscles of 5-day-old male White New Zealand rabbit and based on the purity test using immunocytochemistry (desmin staining) and flow cytometric analysis, more than 97% of the isolated skeletal myoblast have got myogenic phenotype. Myoblast were labelled with PKH26-fluorescent dye and seeded onto the scaffolds and incubated in vitro for 5 days. The in vitro findings of myoblast-seeded BP and BTV scaffolds suggest that myoblast harvested from primary culture are able to form myotube on both types of scaffolds and these naturally derived collagenbased scaffolds showed a tremendous potential for in vitro cultivation of skeletal muscle that can be used as substrate for filling of wound bed or for the delivery of cells. A total of thirty-six male New Zealand white rabbits which were divided into two groups (BP and BTV groups) of eighteen rabbits each were used in this study. The rabbits in each group were further subdivided into two groups of nine rabbits each: the treatment groups (I and II) and control groups (III and IV). Myoblast seeded-BP and myoblast seeded-BTV scaffolds were implanted on the artificially created 3 x 4 cm2 defects at mid-ventral abdominal wall on nine rabbits of the treatment groups I and II, respectively. Whereas, control groups III and IV were repaired with non-seeded BP and BTV scaffolds, respectively. Three rabbits from each group were euthanized at 7th, 14th and 30th days of postimplantation and their ex-implanted specimens were examined macroscopically and microscopically. Macroscopic examination of the abdominal wall post-implantation showed no evidence of herniation, signs of rejection and infection in both treatment and control groups of both type of scaffolds. However, 33.33% and 22.22% mild type of adhesion were found in the control groups III and IV, respectively. Whereas, 11.11% mild type of adhesion and absence of adhesion were found in the treatment groups I and II, respectively. At 7th day of post-implantation, microscopic examinations revealed more intense infiltration of granulocytes and macrophages in the treatment and control groups of both types of scaffolds. Whereas, on 14th and 30th days of post-implantation, the fibroblast migration, deposition of newlyformed collagen, neovascularisation and skeletal muscle cells ingrowths were detected in the treatment groups: I and II. However, not a single of skeletal-muscle cell were found in the control groups III and IV. In conclusion, this study demonstrated that myoblast seeded BP and BTV can be successfully transplanted into abdominal wall defects and resulted in the regeneration of skeletal muscle tissue.